The effects of six-gram D-aspartic acid supplementation on the testosterone, cortisol, and hematological responses of male boxers subjected to 11 days of nocturnal exposure to normobaric hypoxia - Ploszczyca, K.; Czuba, M.; Zakrzeska, A.; Gajda, R. (Nutrients, 2024)
The aim of this study was to evaluate the effects of D-aspartic acid (DAA) supplementation during a simulated altitude protocol on the hormonal and hematological responses in athletes. We hypothesized that DAA supplementation would contribute to an increase in the luteinizing hormone (LH), free, and testosterone and a greater increase in hematological variables. Sixteen male boxers participated; they were randomly assigned to an experimental group (DAA) or a control group (C) and underwent 14 days of supplementation, 6 g/day of DAA. Both DAA and C participants were exposed to normobaric hypoxia (FiO2 = 15.5%; 2500 m) for 10-12 h a day over a period of 11 days. The results showed that DAA had no significant effect on resting, LH, or the testosterone/cortisol ratio during the training camp. Hypoxic exposure significantly (p < 0.05) increased red blood cell and reticulocyte counts as well as hemoglobin and hematocrit concentrations in both groups, but DAA had no significant effect on these changes. In conclusion, we found that DAA supplementation at a dose of 6 g/day for 14 days does not affect the testosterone, cortisol, or hematological responses of athletes during.